PENGEMBANGAN MODUL BERBASIS KEARIFAN LOKAL BANYUWANGI “PENGOLAHAN BIJI KOPI” POKOK BAHASAN SUHU DAN KALOR - Alvi Nurdiniaya; Trapsilo Prihandono; Yushardi Yushardi (JURNAL PEMBELAJARAN FISIKA, 2019)
Abstract Local Wisdom-based module "Coffee Bean Processing" is a form of a fully packaged and systematic teaching material that contains the processing of coffee beans that are associated with temperature and heat material.This type of research is R&D (research and development) development research.The purpose of the study was to analyse the validity and effectiveness of the local wisdom-based module "coffee beans Processing".Module validation consists of a duat stage that is expert validation and user validation.The validation result of the local wisdom based module is 3.58 and the user validation result of 3.78 with the category is very valid.The effectiveness of modules is calculated from cognitive learning outcomes and student learning activities.If the review of the N-gain score, the effective value of the local wisdom-based "coffee beans processing" effectiveness rate is 0.70 and belongs to the high category. Keywords: physics module, local wisdom, validity, effectiveness